Pemanfaatan Tanaman Obat Daerah Menjadi Produk Sabun dan Lilin Untuk Meningkatkan Imunitas di Kabupaten Pamekasan - maasyitoh sari latifah; Myrna Adianti; Maya Septriana; Dessy Harisanty; Edith Frederika Puruhito; Rini Hamsidi; Dwi Setiani Sumardiko; Ario Imandiri (Jurnal SADEWA, 2024)
Based on observations in Pamekasan Regency, many types of medicinal plants were found. Neem leaves (Azadirachta indica) Another plant that is often found in Pamekasan is jasmine (Jasminum grandiflorum L. subsp.). Even though this medicinal ingredient grows a lot in Pamekasan Regency, it has not been utilized optimally. The aim of community service with this workshop is an effort to improve the knowledge of comodity. The targets for implementing this activity are all female students at Al-Mujtama' Islamic boarding school with a total of 75 people. The stages of this activity include: preparation which begins with making initial observations, making pamphlets and preparing materials and tools. The next stage is the implementation stage, training activities in making soap and candles, as well as providing pamphlets on how to make them. The activity lasted for 2 days. The results achieved in addition to community knowledge and skills are products in the form of neem-based soap and aromatherapy candles.